QUALITY OF EDUCATION SERVICES WITH THEIR IMPACT ON STUDENT SATISFACTION (Survey at the Vocational Academy in Bandung City) - Fathur Darajat Surahman; Dedi Mulyasana; Ani Yunaningsih (Holistik Manajemen: Jurnal Manajemen, 2022)
Referring to the importance of the role of tertiary institutions in producing competent graduates who are able to compete in the global era, it is important to provide quality education services. Feeling dissatisfied, satisfied or very satisfied will affect the next action. Students who are satisfied will convey positively about the educational services received. The purpose of this study was to determine how much influence the quality of education services and professional competence had on student satisfaction. The method used in this study is a quantitative method with verification analysis. This study tested the hypotheses to make decisions inductively or generalized, so this research is confirmatory. This study uses a data collection technique that is a questionnaire. Determination of the number of samples used by the author in the study based on the Slovin method because the known population is more than 100 respondents. and analysis using SPSS version 25.The quality of education services partially has a significant effect on student satisfaction. This indicates that if the Quality of Education Services has been prepared and cared for properly, the students at the Vocational Academy in Bandung City will feel satisfied and give a positive response to the campus.